The functional and pragmatic contexts of world Englishes. Issue 1 (9th July 2019) - Valentine, Tamara
Abstract: Drawing on the concepts of the 'context of situation' of J. R. Firth and the Hallidayan meaning of 'linguistic performance', the early works of Braj Kachru presented a sociologically oriented linguistic model to the study of Indian English. Giving Indianness 'functional relevance and formal "manifestation"', Kachru laid the foundation for contextualizing world Englishes within a sociolinguistic framework. This paper revisits the early cultural wars of language, and Kachru's efforts to explain language variation in the multilingual, multicultural contexts of English around the world within the scope of 'pragmatism and linguistic realism' (Kachru, 1986, p. 32). This paper examines the research, studies and insights of scholars who have contributed to furthering the functional and pragmatic contexts in which world Englishes are used.